2019
DOI: 10.21873/invivo.11632
|View full text |Cite
|
Sign up to set email alerts
|

Quality Indicators and Survival Outcome in Stage IIIB-IVB Epithelial Ovarian Cancer Treated at a Single Institution

Abstract: Background/Aim: To investigate the overall survival rate, quality indicators and treatment outcome in FIGO stage IIIB-IVB epithelial ovarian cancer at a University Hospital in Sweden between 2006 and 2015.Materials and Methods: A cohort of 110 patients was followed-up for 3-12 years after cancer diagnosis. Three main groups (primary surgery, neoadjuvant chemotherapy, palliative treatment), and six subgroups were defined according to treatment modality. Results: The mean age was 65 years. Patients were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…However, with the optimization and improvement of treatment methods, more and more patients already have site-distant metastases at initial diagnosis, so it is necessary to adequately evaluate the prognosis of patients by combining the risk of different site-distant metastases. Our study found that organ metastasis had a significant impact on the 5-year overall survival, especially lung, liver and bone metastases, consistent with previous reports [ 18 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, with the optimization and improvement of treatment methods, more and more patients already have site-distant metastases at initial diagnosis, so it is necessary to adequately evaluate the prognosis of patients by combining the risk of different site-distant metastases. Our study found that organ metastasis had a significant impact on the 5-year overall survival, especially lung, liver and bone metastases, consistent with previous reports [ 18 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, with the optimization and improvement of treatment methods, more and more patients already have site-distant metastases at the time of initial diagnosis, so it is necessary to fully evaluate the prognosis of patients by combining the risk of different site metastases. Our study found that organ metastasis had a signi cant impact on the 5-year overall survival time of patients, especially lung, liver and bone metastases, consistent with previous reports 17,22,23 .…”
Section: Discussionsupporting
confidence: 92%
“…By day 40, the number of NCI/ADR-RES cells in all tissues increased further ( Figure 5 B). Overall, we found that the spleen was the organ with the greatest and most consistent extent of metastasis ( Figure 5 B), an organ site that is relevant in the human disease [ 55 ].…”
Section: Resultsmentioning
confidence: 99%